Evaluación del Ruido por tráfico vehicular y su influencia en la calidad de vida en pobladores del distrito Víctor Larco - Cortijo Becerra, Anngie Elizabeth (2023)
The Víctor Larco Herrera district, located in the province of Trujillo, department of La Libertad, presents a growing population every year, according to the INEI for the year 2020, it had a total of 78,304 inhabitants, this district has avenues and main streets with characteristics dynamically commercial. In addition to this, the problems influenced by the expansion of the vehicle fleet and the circulation of vehicles in poor condition are mentioned, being possible sources of noise pollution, since it causes serious problems that affect the environment, health, comfort and quality of life. of the population that carries out their work activities in said district. The purpose of this research work is to evaluate the level of noise from vehicular traffic and the influence it has on the quality of life of the citizens of the Víctor Larco district, through noise monitoring according to the National Environmental Monitoring Protocol, a talk of awareness and a study of perception through surveys, to all this is added a comparative evaluation with the National Standards of Environmental Quality for Noise approved by D.S. 085-2003-PCM. The results obtained from the 15 monitoring stations recorded in three shifts, showed high values in the César Vallejo Extension with Fátima Avenue and Manuel Seoane Avenue with Los Cedros Street with an equivalent sound pressure level of 74.19 dB(A) during the shift. from 7 to 9 am, 79.07 dB(A) in the shift from 12 to 2 pm and in the shift from 6 to 8 pm, 77.58 dB(A) was recorded, where it is evident that the areas most affected and vulnerable to noise pollution are the avenues and streets with the most vehicular traffic. In the case of the survey, a virtual questionnaire applied to a sample of 102 homes was designed, of which 81.4% indicate that vehicular noise is the one that generates the greatest annoyance to the inhabitants of the district, as well as the degree of annoyance caused by the noise. Vehicle noise for 54.9% of the surveyed population is high. However, 86.3% are not aware of the regulations regarding this problem.